Vancomycin-Resistant Enterococcal Infections: Review of Eight Cases - Fatma BAYRAK KENİ; Gönül ŞENGÖZ; Filiz PEHLİVANOĞLU (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2014)
Introduction: With the 1st reportof vancomycin-resistant Enterococcus (VRE) strains in 1988, nosocomial enterococcal infections and epidemics in units such as dialysis, transplantation and ICU started to be reported. Risk factors for VRE infection or colonization are underlying diseases, immunosuppression, prolonged hospital stay, surgical interventions, using broad-spectrum antibiotics, renal failure, and chemotherapy. In this study we evaluated eight cases with VRE growth in urine and blood cultures in 2012. Materials and Methods: Gram-positive cocci were identified by conventional methods, and antibiotic susceptibility to penicillin, ampicillin/sulbactam, gentamicin, teicoplanin and linezolid was tested using Kirby Bauer disc diffusion method in Mueller-Hinton agar (Oxoid, UK) according to CLSI guidelines. Vancomycin-resistant strains were performed in species-level identification using VITEK 2 (BioMerieux, France). Results: VRE grew in blood and/or urine cultures in eight cases. Of those, seven were admitted in the ICU and one in the internal medicine service for 4-90 days. These cases consisted three male and five female subjects aged between 30-84 (median 66). VRE strains were Enterococcus casseliflavus and Enterococcus faecium in one and seven patients, respectively. The earliest and latest identification of VRE growth was in the third and 39th admission day, respectively. All strains were found resistant to penicillin, ampicillin, ampicillin-sulbactam, gentamicin, vancomycin and teicoplanin beside three linezolid-sensitive strains. All VRE cases had history of underlying disease, using broad-spectrum antibiotics including glycopeptides and prolonged hospital stay. Four had history of surgical operation and one had steroid usage seven cases died. Conclusion: Monitoring antibiotic-resistance profile, performing surveillance studies of identified VRE in risky patients, educating hospital staff, close contact isolationand promoting reasonable use of antibiotics are the critical factors for controlling VRE infections.